Pengembangan e-LKPD Berbasis Model Discovery Learning pada Materi Pokok Asam Basa - Pratama, Anugrah; Gani, Tabrani; Danial, Muhammad (Chemistry Education Review (CER), 2021)
This study aims to: (1) determine the process of developing e-LKPD based on the discovery learning model on acid and base materials to improve learning outcomes. (2) determine the level of validity, practicality and effectiveness of e-LKPD based on discovery learning models on acid and base materials to improve learning outcomes. This type of research is Research and Development (R&D). This development research procedure follows the ADDIE model which consists of 5 phases, namely: analysis, design, development, implementation, and evaluation. The results showed that the level of validity of the e-LKPD based on the discovery learning model on the average acid and base material was stated to be very valid and feasible to use. This is based on the results of validation by expert validators with a general validation value of 3.50 or a very valid category. The practicality of the e-LKPD media with the discovery learning model is stated to be practical with a presentation of around 70% - 100%. The e-LKPD media with the discovery learning model is very effective to use. Completeness or achievement of the pretest KKM or those who scored 75 and above were 5 people (13.89%) and increased to 36 student (100%). The developed e-LKPD media contains, (1) title cover, (2) KD and Learning Indicators, (3) brief material, (4) stimulus video, (5) problem formulation column, (6) observation column, (7 ) conclusion column.